Barriers for adherence to diabetic retinopathy screening among Saudi adult population, 2023 - Abdulrahman M. A. Alamri; Manar M. H. Alamri; Rayan A. Alolayani; Shaima Y. A. Assiri; Rayan F. Z. Alshehri; Saud Q. A. Alshabab; Shatha S. M. Alshahrani; Razan S. Aloufi; Amjad M. Al Thamr (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: One common and blinding consequence of diabetes is diabetic retinopathy. However, adherence to regular screening remains a challenge for Saudi adults. The goal of this study is to investigate and identify the barriers that hinder Saudi diabetic adults from adhering to screening for diabetic retinopathy. MATERIALS AND METHODS: This cross-sectional study was conducted in a sample of adult diabetic patients throughout Saudi Arabia. Data was collected using a self-administered validated questionnaire comprising following five primary sections: sociodemographic information, profile of diabetes, knowledge of diabetic retinopathy, behaviors, and hurdles to diabetic retinopathy screening. Sample selected using snowball sampling technique. Questionnaire was converted into Google Forms and was shared with study participants via E-mail and several social media sites, including Facebook and WhatsApp during November and December 2023. Data analyzed using SPSS; mean and standard deviation were calculated for continuous variables, whereas categorical data was presented as frequency and percentage. Logistic regression analysis determined barriers for adherence to screening for diabetic retinopathy. RESULTS: The mean age of the study group was 61.6 ± 15 years, and 58.3% were female. Out of 393 respondents, 71% had undergone retinopathy screening in the past few months; 29.0% had a history of diabetic retinopathy. Participants who knew about retinopathy were eight times more likely to have eye screening compared to those who did not know about retinopathy (odds ratio = 8.05, P < 0.001). Less screening chance was observed among those who had acquired their knowledge from the Internet (odds ratio = 0.23, P = 0.002) or relatives (odds ratio = 0.21, P = 0.002) compared to those who had been advised by their physicians. CONCLUSION: These findings underscored the multifaceted nature of barriers to regular screenings within the Saudi Arabian healthcare system. By understanding and addressing these barriers, healthcare systems can enhance the effectiveness of screening programs and improve health outcomes.